2021
DOI: 10.3389/fmolb.2020.613802
|View full text |Cite|
|
Sign up to set email alerts
|

miR-193a-3p Mediates Placenta Accreta Spectrum Development by Targeting EFNB2 via Epithelial-Mesenchymal Transition Pathway Under Decidua Defect Conditions

Abstract: Objective: To clarify the role of microRNA-193a-3p (miR-193a-3p) in the pathogenesis of placenta accreta spectrum.Methods: The placental tissue expression levels of miR-193a-3p and Ephrin-B2 (EFNB2) were compared between a placenta accreta spectrum group and a control group. Transwell migration and invasion assays were used to verify the effect of miR-193a-3p and EFNB2 on HTR-8/SVneo cells cultured in human endometrial stromal cell (hESC)-conditioned medium. Epithelial-mesenchymal transition (EMT)-related prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…However, the specific role of these molecules in the pathogenesis of PAS has not been completely elucidated. [9][10][11] Hence, it is imperative to identify the relevant proteins and pathways affecting placental implantation for further prediction and intervention. Laminins are in the basement membrane protein family and prior studies have shown that laminins are engaged in placental development and regulate placental trophoblast cell functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the specific role of these molecules in the pathogenesis of PAS has not been completely elucidated. [9][10][11] Hence, it is imperative to identify the relevant proteins and pathways affecting placental implantation for further prediction and intervention. Laminins are in the basement membrane protein family and prior studies have shown that laminins are engaged in placental development and regulate placental trophoblast cell functions.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulating evidences have confirmed that molecular and phenotypic similarities between PAS and cancer. However, the specific role of these molecules in the pathogenesis of PAS has not been completely elucidated 9–11 . Hence, it is imperative to identify the relevant proteins and pathways affecting placental implantation for further prediction and intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our finding was in an agreement with Yang et al in which we found that miR-23a could function as a potential biomarker in the first trimester of GDM. On the other hand, upregulated miR193a has been shown to play a vital role in the pathogenesis of placenta accreta spectrum development mediated by the target in EFNB2 gene via the EMT signaling pathway 26 . In addition to that, elevated miR193a was reported as a potentially new biomarker for the diagnosis of diabetic nephropathy 27 .…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 In cases of PAS, several miRs play a role in pathogenesis, including miR-34a, -125a, -193a, and -518b. 24 , 25 , 26 , 27 However, miR data for PAS are limited. Chen et al 28 have shown potential benefit in using a 4 miR PAS signature in a small cohort of patients with placenta increta or percreta.…”
Section: Introductionmentioning
confidence: 99%